Overcoming dormancy of Passiflora elegans Mast. (Passifloraceae) seeds - Silva, Aparecida Leonir da; Hilst, Paulo César; Dias, Denise Cunha Fernandes dos Santos; Rogalski, Marcelo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The seeds of Passiflora present low and ununiform germination, due to the presence of seed dormancy, so this dormancy must be overcome by an efficient method that increases germination rates. This study was conducted to evaluate the efficiency of methods for overcoming dormancy of Passiflora elegans seeds. Thirty-five ripe fruits were collected in the municipality of Getúlio Vargas, Rio Grande do Sul in December 2013. The experiment was conducted at the Universidade Federal de Viçosa. The following methods were used to overcome dormancy: T1: seeds with tegument; T2: seeds without tegument; T3- mechanical scarification; T4: chemical scarification in concentrated sulfuric acid for 10 min; T5: stratification for 5 days at 4 °C; T6: seeds without the integument, followed by immersion in gibberellic acid GA3 (50 μM); T7: seeds without the integument, followed by immersion in paclobutrazol solution (0.1 mM). The seeds were submitted to germination test, using five replicates of 40 seeds, kept in B.O.D. at 25 °C. Germination was evaluated daily for 80 days. Were evaluated the germination percentage, speed of germination index (IVG) and speed of germination (VG). In the tetrazolium test the seeds received a pickle and were placed to soak for 16 h and cut lengthwise and immersed in 0.05% tetrazolium solution and kept in the dark in a water bath at 36 °C for 24 h. It was concluded that immersion of the seeds in GA3 (50 μM) is the best method to overcome the dormancy of P. elegans.